The mediating effect of change management - Filep, Roland (Marketing & Menedzsment, 2026)
THE AIM OF THE PAPER This study investigates the impact of transformational leadership on organizational performance through change management. It investigates which leadership behaviours and change-management steps drive this effect and how it differs across financial and non-financial performance dimensions in SMEs using the Balanced Scorecard. METHODOLOGY Regression-based mediation analyses were applied to test overall and dimension-specific effects. Q1–Q4 guided the examination of leadership dimensions, change management steps, and performance outcomes, including phase-specific effects during execution and institutionalization. MOST IMPORTANT RESULTS Transformational leadership has a positive impact on organizational performance, primarily through change management. Mediation is strongest in the execution and institutionalization phases, especially for behaviours that engage and empower employees, and is more pronounced for non-financial outcomes. RECOMMENDATIONS Leaders should adopt a transformational style and focus on leadership behaviours and change-management practices that are the most effective during the execution and institutionalization phases. Employee involvement in these phases is critical, and leadership development programs should emphasize these competencies to enhance sustainable performance.